Acceleration of Deep Slip Along the Longmenshan Fault Plane Before the 2008 M8.0 Wenchuan Earthquake - Zhao, Jing; Yuan, Zhengyi; Ren, Jinwei; Jiang, Zaisen; Yao, Qi; Zhou, Zhihua; Yue, Chong; Zhong, Jun; Niu, Anfu (Frontiers in Earth Science, 2022)
The first step toward earthquake forecasting is the identification of variables whose spatio-temporal variation can be connected with pre-seismic crustal deformation. Four periods of campaign Global Positioning System (GPS) observations around the Longmenshan fault zone (LFZ) provide important insights in crustal deformation and deep fault slip before the 2008 M8.0 Wenchuan earthquake. By using TDEFNODE to invert the coupling fraction and dynamic slip deficit rate of the Longmenshan fault plane before the Wenchuan earthquake, we show that under a background of strong coupling, the compressive slip deficit rate perpendicular to fault increased slightly at first and then decreased; a value of 1.5–3.6 mm/a along the central–southern segment from 1999 to 2001 increased to ~1.9–3.9 mm/a from 2001 to 2004, and then decreased to ~1.1–2.6 mm/a from 2004 to 2007. The dextral slip deficit rate parallel to fault was ~6 mm/a from 1999 to 2004, before increasing significantly to ~9.5 mm/a from 2004 to 2007, when the compressive slip deficit rate decreased. At the same time, large-scale GPS velocity profiles show that compressive shortening deformation in the Eastern Tibet Block, perpendicular to fault, increased slightly from 2001 to 2004, and then decreased from 2004 to 2007. Meanwhile, the dextral shear deformation parallel to fault near the LFZ increased significantly from 2004 to 2007. These findings are in good agreement with those calculated using repeating earthquake sequences, indicating that the deep slip rate of the Longmenshan fault plane may have accelerated several years before the Wenchuan earthquake. Our results demonstrate that GPS data can record pre-seismic preparatory processes, and have the potential for use in medium-term large earthquake forecasting.